CEMARAN BAKTERI MESOFILIK AEROBIK PADA CEKER AYAM DALAM SOTO DARI TIGA LOKASI RUMAH MAKAN DI BANDA ACEH (Mesophilic Aerobic Bacteria Contamination of chicken shank in soto from three restaurant locations in Banda Aceh) - Teuku Reza Ferasyi; Razali Razali; Safarwati Safarwati; Nurliana Nurliana; Sulasmi Sulasmi; T. Armansyah (Jurnal Medika Veterinaria, 2015)
This study was aimed to test the level of mesophilic aerobic bacteria contamination on chicken shank in "soto" food from restaurants in three different locations, Inong Balee-Darussalam, Ulee Kareng, and Campus of Unsyiah. A purpossive sampling method was used in this study. The sample of chicken shank in soto were collected in the morning at 10.00 a.m. and in the afternoon at 14.00 p.m. Samples were collected for 3 consecutive days. For each sampling, a total of 25 grams of chicken shank was put into plastic bag and directly transfer to the Veterinary Public Health Laboratory, Faculty of Veterinary Medicine of Syiah Kuala University. The result showed that the chicken shank in the soto food from three locations of restaurant had been contaminated with mesofilic aerobic bacteria with contamination level exceeds the maximum limit of microbial contamination as allowed in SNI - 2000.Key words: soto, shank, restaurants